Development of an Ethnoscience-Based Integrated Science Module with RIAS Learning Model to Improve Students' Critical Thinking Ability - Fadilah, Arum Maharsi; Muhlisin, Ahmad; Ismawati, Riva (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
The ability to think critically is an important competency that students must have in the 21st century, especially in the implementation of Curriculum Merdeka. However, in practice, there is a lot of learning process without training to improve critical thinking skills. So a solution is needed, namely the development of teaching materials such as modules that can overcome this problem. This research uses the Hannafin & Peck model development research form. The product is an integrated science module based on ethnoscience aspects at the Nglipoh Magelang pottery industry. This module is also integrated with the RIAS learning model which also facilitates students' critical thinking skills. The validity test obtained results of 3.32 from media experts and 3.66 from material experts so it is declared very valid. The effectiveness test with an N-Gain obtained a result of 0.74, so it can be concluded to be very effective. The practicality of the module was also analyzed based on a questionnaire with a result of 83.18% so it can be concluded that this module is very practical to use. The conclusion of this research is that the module is suitable for implementation to improve students' critical thinking skills.